The three musketeers - Dumas, Alexandre, 1802-1870.; Bair, Lowell (New York : Bantam Dell, 2004)
During the reign of France's King Louis XIII, D'Artagnan and three musketeers unite to defend the honor of Anne of Austria against the plots of Cardinal Richelieu.
"Complete and unabridged"--Cover.
Translation of: Les trois mousquetaires.
Adult
Young Adult.
Keywords: Swordplay -- Fiction; Adventure fiction; Swordplay -- Fiction; France -- History -- Louis XIII, 1610-1643 -- Fiction; France -- History -- 1589-1789, Bourbons -- Fiction; Adventure fiction